Responding to the need of postgraduate education for Planetary Health: Development of an online Master's Degree - O'Callaghan-Gordo, Cristina; Moreno, Ariadna; Bosque-Prous, Marina; Castro-Sanchez, Enrique; Dadvand, Payam; Guzmán, Carlos A. Faerron; García-Juanatey, Ana; Gascon, Mireia; Grau, Oriol; Jordana, Jacint; Lowe, Rachel; March, Hug; et al. (Frontiers in Public Health, 2022)
Planetary Health has emerged as a new approach to respond to the existential risks that the clime and global environmental crises pose to human societies. As stated by various stakeholders, the challenges involved in Planetary Health are of such magnitude that education must be at the forefront to obtain a meaningful response. Universities and higher education institutions have been specifically called to embed the concept of planetary stewardship in all curricula and train the next generation of researchers and changemakers as a matter of urgency. As a response to this call, the Universitat Oberta de Catalunya (UOC), the Universitat Pompeu Fabra (UPF), and the Barcelona Institute for Global Health (ISGlobal) developed the first online and asynchronous Master in Science (MSc) in Planetary Health. The aim of the programme is to train a new generation of academics and professionals who understand the challenges of Planetary Health and have tools to tackle them. This article describes the development of the curriculum of this MSc, presents the main characteristics of the programme and discusses some of the challenges encountered in the development of the programme and its implementation. The design of this MSc was based on: the alignment of the programme with the principles for Planetary Health education with a focus on human health; a multi-, inter-, and trans-disciplinary approach; the urgency to respond to the Anthropocene challenges; and the commitment to the 2030 Agenda. The MSc was recognized as an official degree by the Agency for Quality of the Catalan University System, included in the European Quality Assurance Register for Higher Education, and the Spanish National Academic Coordination body in April 2021 and launched in October 2021. There are currently more than 50 students enrolled in the program coming from a broad range of disciplines and geographic locations. The information presented in this article and the discussion on challenges encountered in developing and implementing the programme can be useful for those working in the development of similar programs.